Evaluation of proxy tests for SFSN: evidence for mixed small and large fiber dysfunction. - Hamid Ebadi; Bruce A Perkins; Hans D Katzberg; Leif E Lovblom; Vera Bril (PLoS ONE, 2012)
BACKGROUND: Though intra-epidermal nerve fiber density (IENFD) is considered the gold standard for diagnosis of small fiber sensory neuropathy (SFSN), we aimed to determine if novel threshold values derived from standard tests of small or large fiber function could serve as diagnostic alternatives. METHODS: Seventy-four consecutive patients with painful polyneuropathy and normal nerve conduction studies (NCS) were defined as SFSN cases or controls by distal IENFD <5.4 and ≥5.4 fibers/mm, respectively. Diagnostic performance of small fiber [cooling (CDT) and heat perception (HP) thresholds, axon reflex-mediated neurogenic vasodilatation] and large fiber function tests [vibration perception thresholds (VPT) and sural nerve conduction parameters] were determined by receiver operating-characteristic (ROC) curve analyses. RESULTS: The 26(35%) SFSN cases had mean IENFD 3.3±1.7 fibers/mm and the 48(65%) controls 9.9±2.9 fibers/mm. Male gender (p = 0.02) and older age (p = 0.02) were associated with SFSN cases compared to controls. VPT were higher and CDT lower in SFSN cases, but the largest magnitude of differences was observed for sural nerve amplitude. It had the greatest area under the ROC curve (0.75) compared to all other tests (p<0.001 for all comparisons) and the optimal threshold value of ≤12 µV defined SFSN cases with 80% sensitivity and 72% specificity. CONCLUSION: In patients presenting with polyneuropathy manifestations and normal NCS, though small fiber function tests were intuitively considered the best alternative measures to predict reduced IENFD, their diagnostic performance was poor. Instead, novel threshold values within the normal range for large fiber tests should be considered as an alternative strategy to select subjects for skin biopsy in diagnostic protocols for SFSN.